EFFECT OF RELIGIOSITY, PREVENTION FOCUS, FUTURE ORIENTATION, AND FINANCIAL KNOWLEDGE ON PURCHASE INTENTION TO LONG-TERM INVESTMENT IN SHARIA INSURANCE - Kusumajati W.; Syah T.Y.R.; Kustiawan U.; Negoro D.A.; Tegor (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
This research aims to examine the effect of religiosity on purchase intention to long-term investment in sharia insurance which is moderated by prevention focus, future orientation, and financial knowledge. This research applies a non-hierarchical analysis method or cell mean method using between subject 2×2 and the procedure of Univariate General Linear (GLM) Model. The first research finding found that religiosity has significantly affected purchase intention to long-term investment in sharia insurance; thus, H1 has supported the hypothesis. The second finding showed that high religiosity which is moderated by low prevention focus increases purchase intention to long-term investment in sharia insurance; thus, H2a has supported the hypothesis. However, religiosity which is moderated by high prevention focus does not support the hypothesis, thus, H2b and H2c are not proven. The third finding found that religiosity which is moderated by future orientation has shown very significant result, thus, the H3a, H3b, and H3c hypotheses have been proven to support the hypothesis. The fourth findings showed that high religiosity which is moderated by low financial knowledge has been proven to affect purchase intention to long-term investment in sharia insurance; so, H4a has supported the hypothesis. However, religiosity which is moderated by high financial knowledge has not supported the hypothesis; thus, H4b and H4c is not proven.